Stimulation in primary and secondary metabolism by elevated carbon dioxide alters green tea quality in Camellia sinensis L - Xin Li (Nature Portfolio, 2017)
Abstract Rising CO2 concentration, a driving force of climate change, is impacting global food security by affecting plant physiology. Nevertheless, the effects of elevated CO2 on primary and secondary metabolism in tea plants (Camellia sinensis L.) still remain largely unknown. Here we showed that exposure of tea plants to elevated CO2 (800 µmol mol−1 for 24 d) remarkably improved both photosynthesis and respiration in tea leaves. Furthermore, elevated CO2 increased the concentrations of soluble sugar, starch and total carbon, but decreased the total nitrogen concentration, resulting in an increased carbon to nitrogen ratio in tea leaves. Among the tea quality parameters, tea polyphenol, free amino acid and theanine concentrations increased, while the caffeine concentration decreased after CO2 enrichment. The concentrations of individual catechins were altered differentially resulting in an increased total catechins concentration under elevated CO2 condition. Real-time qPCR analysis revealed that the expression levels of catechins and theanine biosynthetic genes were up-regulated, while that of caffeine synthetic genes were down-regulated in tea leaves when grown under elevated CO2 condition. These results unveiled profound effects of CO2 enrichment on photosynthesis and respiration in tea plants, which eventually modulated the biosynthesis of key secondary metabolites towards production of a quality green tea.